Inoculation with Roseovarius increases thermal tolerance of the coral photosymbiont, Breviolum minutum - Heric, Karla; Maire, Justin; Deore, Pranali; Perez-Gonzalez, Alexis; van Oppen, Madeleine J. H. (Frontiers in Ecology and Evolution, 2023)
Coral reefs are diverse marine ecosystems that have tremendous ecological and cultural value and support more than 25% of eukaryote marine biodiversity. Increased ocean temperatures and light intensity trigger coral bleaching, the breakdown of the relationship between corals and their photosymbionts, dinoflagellates of the family Symbiodiniaceae. This leaves corals without their primary energy source, thereby leading to starvation and, often, death. Coral bleaching is hypothesized to occur due to an overproduction of reactive oxygen species (ROS) by Symbiodiniaceae, which subsequently accumulate in coral tissues. Bacterial probiotics have been proposed as an approach to mitigate coral bleaching, by reducing ROS levels in the coral holobiont through bacterial antioxidant production. Both corals and Symbiodiniaceae are known to associate with bacteria. However, the Symbiodiniaceae-bacteria relationship, and its impact on Symbiodiniaceae thermal tolerance, remains a poorly studied area. In this study, cultured Symbiodiniaceae of the species Breviolum minutum were treated with antibiotics to reduce their bacterial load. The cultures were subsequently inoculated with bacterial isolates from the genus Roseovarius that were isolated from the same B. minutum culture and showed either high or low ROS-scavenging abilities. The B. minutum cultures were then exposed to experimental heat stress for 16 days, and their health was monitored through measurements of cell density and photochemical efficiency of photosystem II. It was found that B. minutum inoculated with Roseovarius with higher ROS-scavenging abilities showed greater cell growth at elevated temperatures, compared to cultures inoculated with a Roseovarius strain with lower ROS-scavenging abilities. This suggests that Roseovarius may play a role in Symbiodiniaceae fitness at elevated temperatures. Analysis of Symbiodiniaceae-associated bacterial communities through 16S rRNA gene metabarcoding revealed that Roseovarius relative abundance increased in B. minutum cultures following inoculation and with elevated temperature exposure, highlighting the contribution they may have in shielding B. minutum from thermal stress. This study begins to unpick the relationship between Symbiodiniaceae and their bacteria and opens the door for the use of Symbiodiniaceae-associated bacteria in coral reef conservation approaches.